2002
DOI: 10.1200/jco.2002.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Weekly Single-Agent Paclitaxel in Platinum/Paclitaxel-Refractory Ovarian Cancer

Abstract: Weekly paclitaxel (80 mg/m(2)) is generally well tolerated and is an active second-line regimen against ovarian cancer that has demonstrated resistance to platinum/paclitaxel delivered on an every-3-week schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(98 citation statements)
references
References 14 publications
5
90
0
3
Order By: Relevance
“…The median TTP and OS in our platinum-resistant patients were only 3 months and 9 months respectively. These were slightly lower than 4-6 months for TTP and 8-14 months for OS found in other studies which used either weekly (Thirapakawong et al, 2001;Markman et al, 2002;Ghamande et al, 2003) and were comparable to the corresponding figures of 4 months and 9 months from the studies which used the tri-weekly schedule (Trimble et al, 1993;Thigpen et al, 1994).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The median TTP and OS in our platinum-resistant patients were only 3 months and 9 months respectively. These were slightly lower than 4-6 months for TTP and 8-14 months for OS found in other studies which used either weekly (Thirapakawong et al, 2001;Markman et al, 2002;Ghamande et al, 2003) and were comparable to the corresponding figures of 4 months and 9 months from the studies which used the tri-weekly schedule (Trimble et al, 1993;Thigpen et al, 1994).…”
Section: Discussionmentioning
confidence: 55%
“…We could demonstrate the response of 12.5% in eight evaluable patients of this group. Previous studies showed 16-62% response rate of platinum-resistant disease having paclitaxel (McGuire et al, 1989;Trimble et al, 1993;Thigpen et al, 1994;Thirapakawong et al, 2001;Markman et al, 2002;Ghamande et al, 2003;Kita et al, 2004;Linch et al, 2008). The difference of treatment outcome may be due to the limited number of patients in this particular group of patient.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Paclitaxel, as single agent, represents to date, a good clinical option in term of RR and survival, in particular if we consider weekly schedule [38,39]. Furthermore, the albumin-bound formulation of paclitaxel, nab-paclitaxel too, has been investigated in this setting showing similar RR (23%) and a median PFS of 4.7 months with a good tolerability [40].…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…Low-dose cyclophosphamide administered every 6 days had better therapeutic effects than higher doses given every 21 days [53]. Similarly, in clinical trials, weekly taxane chemotherapy has been shown to result in a high rate of objective responses even in individuals with chemotherapy-resistant ovarian cancers [54]. Certain cytotoxic agents, such as vinblastine, cyclophosphamide, and taxanes, have anti-angiogenic properties when administered at 10% to 20% of the MTD in combination with an anti-VEGFR-2 antibody [55].…”
Section: Anti-angiogenic Scheduling Of Chemotherapymentioning
confidence: 99%